1987
DOI: 10.1113/jphysiol.1987.sp016841
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone selectively increases sodium‐dependent alanine transport across neonatal piglet intestine.

Abstract: SUMMARY1. Lysine and alanine uptake by pig enterocytes has been measured in piglet mid intestine both during normal development and 3 days after injection of dexamethasone and epidermal growth factor (EGF) into 3-day-old animals.2. Alanine uptake measured in the presence of sodium increased markedly during the first 4 weeks of post-natal life. Similar effects on alanine uptake could be produced through injection of dexamethasone, but not EGF, into 3-day-old piglets. Alanine uptake measured in the absence of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The small intestine was then quickly removed and samples taken 25, 50 and 75 % along the length for biochemical and cytochemical determination of disaccharidase and alkaline phosphatase activities. Piglets used in these experiments were identical to those described previously when determining the effect of EGF and dexamethasone on amino acid transport (James et al 1987a). …”
Section: Methodsmentioning
confidence: 99%
“…The small intestine was then quickly removed and samples taken 25, 50 and 75 % along the length for biochemical and cytochemical determination of disaccharidase and alkaline phosphatase activities. Piglets used in these experiments were identical to those described previously when determining the effect of EGF and dexamethasone on amino acid transport (James et al 1987a). …”
Section: Methodsmentioning
confidence: 99%
“…MP inhibits many of the major immune pathways (13,51). MP and other glucocorticoids have been shown to reverse the inhibition of nutrient and electrolyte malabsorption in animal models of IBD or Crohn's disease (7,10,16,17,30,32,33,36,43,46). For example, we have demonstrated that SGLT1 (43), ASCT1 (46), and the Na-K-ATPase inhibition (43,46) are reversed by MP in a rabbit model of chronic ileal inflammation.…”
mentioning
confidence: 75%
“…Because MP increases the mRNA levels of ASBT as well as the immunoreactive protein levels of ASBT in the BBM of villus cells, the likely mechanism of stimulation of ASBT in villus cells in the normal ileum is secondary to increased number of cotransporters. Indeed, other studies have also concluded that, in the normal intestine, MP may regulate Na-solute cotransport and electrolyte transport pathways directly (16,17,27,32,36). However, glucocorticoids do not indiscriminately stimulate all Na-solute cotransport processes.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for estimating crypt depth, villus length and villus area were based on those described previously (James, Smith, Tivey & Wilson, 1987 All pigs received a final meal, corresponding to 2 % of their body weight, 18 h before the start of the infusion protocol and 24 h before the end of the experiment. Littermate pairs of similar body weight had been selected at 3 weeks of age, and since they grew at similar rates throughout the 3 weeks of investigation, mean body weights on the day of experiment were not significantly different between controls and their littermates treated with T3 (7 7 + 0 4 and 7 9 + 0 4 kg respectively).…”
Section: Methodsmentioning
confidence: 99%